STABILISASI TANAH GAMBUT MENGGUNAKAN ABU BOILER KELAPA SAWIT DITINJAU DARI NILAI CBR LABORATORIUM - Fenny Bernavida; Sri Wulandari (Rekayasa Sipil, 2021)
Palm oil boiler ash is the waste from the palm oil boiler combustion which contains a lot of silicates. In addition, palm oil boiler ash also contains inorganic cations such as potassium and sodium. Palm oil boiler ash is pozzolanic material, which is a non-binding material such as cement, but contains active Silica Oxide (SiO2) compounds which when reacted with free lime or calcium hydroxide (Ca (OH2)) and water will form materials such as cement, namely calcium Silica Hydrate. In this study, we will use palm oil boiler ash waste which has been stated to have good soil improvement results as a mixture of peat soil improvement in the hope of getting better improvement results from previous studies in terms of California Bearing Ratio values. The boiler ash to be used is a variation of the mixture of 0%, 5%, 10% and 15% to the weight of the soil sample and using 28 days treatment. The California Bearing Ratio value of the original peat soil is 0.247%, the percentage of 5% increases to 0.433%, at the percentage of 10% is 0.629% and at the percentage of 15% is 0,729%.